2015
DOI: 10.11648/j.ijnfs.20150402.14
|View full text |Cite
|
Sign up to set email alerts
|

LC-MS/MS Based Metabolomics to Identify Biomarkers Unique to Laetiporus sulphureus

Abstract: LC/MS/MS technique, employing QTOF mass analyzer, was used for comparative metabolomic fingerprinting of seven edible mushroom varieties (P.ostreatus, L.edodes, L.sulphureus, A.campestris, T.clypeatus, T.microcarpus and T.letestui). The aim was to identify biomarkers unique to L.sulphureus which might be responsible for the pharmacological claim of the mushroom by the Kaffa people in Ethiopia. As an outcome of the data mining and pre-treatment step using Markerview TM software, positive and negative ionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Metabolomics approaches by means of mass spectrometry (MS) have been gaining interest not only for analysis of plants, but also for mushrooms [14,15]. Gas chromatography-mass spectrometry (GC/MS) is a platform which is frequently used in metabolomic studies for the analysis of primary metabolites, whereas liquid chromatography-mass spectrometry (LC/MS) is commonly used for the analysis of secondary metabolites [16].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomics approaches by means of mass spectrometry (MS) have been gaining interest not only for analysis of plants, but also for mushrooms [14,15]. Gas chromatography-mass spectrometry (GC/MS) is a platform which is frequently used in metabolomic studies for the analysis of primary metabolites, whereas liquid chromatography-mass spectrometry (LC/MS) is commonly used for the analysis of secondary metabolites [16].…”
Section: Introductionmentioning
confidence: 99%
“…The metabolome of L. sulphureus was compared with that of seven edible fungi, including P. ostreatus, to identify biomarkers that could be related to the production of metabolites of industrial interest. Woldegiorgis et al 2015…”
Section: Joh Et Al 2007mentioning
confidence: 99%
“…Organic acids, sugars/sugar alcohols and amino acids were depicted to be the three main metabolite families. Woldegiorgis et al (2015) reported the use of LC/MS/MS equipped with a QTOF mass analyzer for the comparative metabolite profiling of seven edible mushroom varieties including P. ostreatus, A. campestris, L. edodes, L. sulphureus, T. microcarpus T. clypeatusand T. letestui, and identified biomarkers relevant to L. sulphureus. 18 α-Glycyrrhetinic acid was revealed to be one of the potential metabolites which might be responsible for the biological/pharmacological claim of understudy mashrooms by the local people.…”
Section: Analytical Tools For Metabolite Profilingmentioning
confidence: 99%